Crystallization of 2D Hybrid Organic–Inorganic Perovskites Templated by Conductive Substrates. (20th January 2021) - Kovaricek, Petr; Nadazdy, Peter; Pluharova, Eva; Brunova, Alica; Subair, Riyas; Vegso, Karol; Guerra, Valentino Libero Pio; Volochanskyi, Oleksandr; Kalbac, Martin; Krasnansky, Alexander; Pandit, Pallavi; Roth, Stephan Volker; et al.
Abstract: 2D hybrid organic–inorganic perovskites are valued in optoelectronic applications for their tunable bandgap and excellent moisture and irradiation stability. These properties stem from both the chemical composition and crystallinity of the layer formed. Defects in the lattice, impurities, and crystal grain boundaries generally introduce trap states and surface energy pinning, limiting the ultimate performance of the perovskite; hence, an in‐depth understanding of the crystallization process is indispensable. Here, a kinetic and thermodynamic study of 2D perovskite layer crystallization on transparent conductive substrates are provided—fluorine‐doped tin oxide and graphene. Due to markedly different surface structure and chemistry, the two substrates interact differently with the perovskite layer. A time‐resolved grazing‐incidence wide‐angle X‐ray scattering (GIWAXS) is used to monitor the crystallization on the two substrates. Molecular dynamics simulations are employed to explain the experimental data and to rationalize the perovskite layer formation. The findings assist substrate selection based on the required film morphology, revealing the structural dynamics during the crystallization process, thus helping to tackle the technological challenges of structure formation of 2D perovskites for optoelectronic devices. Abstract : Conductive substrates are essential components of optoelectronic devices based on 2D hybrid organic–inorganic perovskites. They provide electrical contact but also influence the crystallinity of the perovskite layer. The influence of two representative conductive substrates, FTO and graphene, on the crystallization of the epitaxial perovskite layer is investigated by GIWAXS and computational methods to rationalize the substrate choice for a particular device.